The Role of Renewable Energy Production, Energy Efficiency and Green Finance in Achieving Sustainable Economic Development: Evidence from Indonesia - Tiawon, Harin; Miar, Miar (International Journal of Energy Economics and Policy, 2023)
The current study aims at analyzing the effect of renewable energy production, energy efficiency and green finance on sustainable economic development in Indonesia. The study is the pioneer one in the context of Indonesia that assesses the impact of above-mentioned variables on measuring sustainable economic development by measuring it in terms of economic growth and carbon emission. Time series data spanning over 1990-2019 period is analyzed using Autoregressive Distributed Lag Model (ARDL) because of presence of the mixed order of integration in data series. The findings of the study suggest that green finance, energy efficiency and renewable energy promote economic growth and reduce carbon emissions. The study concludes that renewable energy production, green finance and energy efficiency play positive role in achieving sustainable economic development in Indonesia. On the basis of the study findings, relevant policies for the government and policy makers to enhance sustainable economic development in Indonesia are also provided in the study.